The Evaluation of the Effectiveness of the Tajwid Mushawwar Application in Improving the Pronunciation of Makharijul Huruf in Students of the Idad Lughawi Program - Ramadlani, Muhammad Tsalis; Nurrohim, Ahmad; Haq, Yusdi; Bahar, Alexander; Faruqi, Fahmi; Nurisnaini, Binti; Taqnaing, T (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to evaluate the effectiveness of the Tajwid Mushawwar application in improving the pronunciation ability of makharijul huruf in Idad Lughawi Program students. The research method used is pre-experimental designs with a one-group pretest-posttest model. A total of 30 Idad Lughawi Program students became the subjects of the study. The study was conducted for a certain period, and data were collected through pre-tests and post-tests that measured the pronunciation ability of makharijul huruf. In addition, student response questionnaires were also used to explore students' perceptions, comfort, and motivation in using the Tajwid Mushawwar application. The results of the data analysis showed a significant increase in the pronunciation ability of makharijul huruf after students used the Tajwid Mushawwar application. In addition, positive responses from the student response questionnaire indicated that this application was considered to help understand concepts, increase motivation, and provide comfort in learning. This study contributes positively to the literature on the development of Arabic language learning methods, especially in the pronunciation of makharijul huruf. The practical implications of this research can be used as a basis for further development related to the use of technology in Arabic language learning and enriching the insights of teachers and developers of learning applications.